Implementasi Etika Kristen Dalam Keluarga Badan Pengurus Jemaat Gereja Kemah Injil Indonesia Propinsi Jawa Tengah - Jamin Tanhidy; Muner Daliman; Hana Suparti; Krido Siswanto (Sekolah Tinggi Teologi Simpson, 2021)
Family institution as the smallest unit of the human institutional system, like an organization, need rules and a code of ethics in order to run well. If ethics is not consistently applied in a family, it will have a negative impact on the harmony and quality of family, which in turn has a bad impact on the church, school, community and nation. Therefore, the aim of this Applied Research is to find out the level and what the most dominant indicators that tend to determine the implementation of Christian Ethics in the Family of the Church Leaders of Alliance Church in Central Java Province. This research using Quantitative Method based on aexegetical study text from Ephesians 5: 22-6: 4 in order to find out the indicators that determine the research. About 120 people are taking as a sample, using the Non Random Sampling Technique, data computed by SPSS Programme version 20. The result showed that, first, the level of implementation of Christian ethics in the family based on Ephesians 5: 22-6: 4 among The Church Leaders of Alliance Church in Central Java Province is in the category